Studi Pemanfaatan Ruas Bambu Sebagai Bilah Sudu-sudu Turbin Pelton untuk Peningkatan Teknologi Energi Pedesaan Guna Mendukung Program Desa Mandiri Energiâ - , MUHIBBUDDIN; , Ir. Samsul Kamal, M.Sc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Pelton turbine is an impulse type turbine that has not been developed for rural are as in particular which have ascale hydropower potential with a high potential for water fall (head). Its quite large but with the flow (flow) Q is relatively small. This Pelton turbine use bamboo blade so that it has several potential advantages such as bamboo which is pretty muchalmostall regions, simple construction, and easy operation, low maintenance cost and environmentally friendly. This study aimed to design a model Pelton turbine blade bamboo and its performance towards power output and efficiency. In this study the ability of bamboo is investigated which will formin converting the kinetic energy of the nozzle into the next torque with intermediate wheel and generator into electrical energy. The basic principle of impulse turbine type (in this case taken Pelton type turbines) will serve as the basis of analysis in which a handful of split bamboo will function as the Pelton turbine blades. The geometry of water jets (jet) will be varied with the geometry of square and round shapes to see which one best match with the geometry of parts of the bamboo. No-load test results show that the model Pelton turbine blade bamboo with square nozzles produce a higher rotation of the 131.40 rpm than a bolt nozzle with the same area on the head, H and discharge, Q that are 9.15 m and 0.0064 mÂ³/s. On the test results with the load, square nozzle gives best performance to power output and efficiency. The power output increases 15,95 watt and efficiency increases 6.01% compared with a bolt nozzle in the same head, H and discharge, Q. This is caused by the emission factor of the water (jet) in which the square nozzle strike field of bamboo blade a concave shape wider,making a greater energy conversion.